2021
DOI: 10.1016/j.amepre.2020.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Use of Machine Learning to Determine the Information Value of a BMI Screening Program

Abstract: Introduction: Childhood obesity continues to be a significant public health issue in the U.S. and is associated with short-and long-term adverse health outcomes. A number of states have implemented school-based BMI screening programs. However, these programs have been criticized for not being effective in improving students' BMI or reducing childhood obesity. One potential benefit, however, of screening programs is the identification of younger children at risk of obesity as they age.Methods: This study used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Marcos-Pasero used random forest (RF) and gradient boosting to predict the BMI from 190 multidomain variables (data collected from 221 children aged 6 to 9 years) and determined the relative importance of the predictors [ 25 ]. Zare et al used kindergarten-level BMI information, demographic, socioeconomic information such as family income, poverty level, race, ethnic compositing, housing, parent education, and family structure to predict obesity at the fourth grade and achieved an accuracy of about 87% by using logistic regression and an artificial neural network [ 26 ]. This study also reported that the kindergarten BMI Z-score is more important for BMI prediction than the demographic and socioeconomic variables.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Marcos-Pasero used random forest (RF) and gradient boosting to predict the BMI from 190 multidomain variables (data collected from 221 children aged 6 to 9 years) and determined the relative importance of the predictors [ 25 ]. Zare et al used kindergarten-level BMI information, demographic, socioeconomic information such as family income, poverty level, race, ethnic compositing, housing, parent education, and family structure to predict obesity at the fourth grade and achieved an accuracy of about 87% by using logistic regression and an artificial neural network [ 26 ]. This study also reported that the kindergarten BMI Z-score is more important for BMI prediction than the demographic and socioeconomic variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We choose random forest, artificial neural networks, logistic regression, support vector machine, k -nearest neighbors, and k -means clustering because they are the most commonly used ML algorithms in the decision tree, neural network, probability of occurrence, hyperplane, neighborhood, and unsupervised learning based categories, respectively. These algorithms have been widely used in previous studies for predicting obesity [ 20 , 22 , 23 , 25 , 26 , 31 ]. Although these six ML algorithms have been used in multiple studies, the implementation approaches differ from one study to another.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, of the 3090 articles identified initially through the keyword search, 46 (1.49%) were included in the review . [28,32,33,37,42,46,48,[50][51][52][53]57,58,60,62,63]; 6 (13%) in China [39,40,45,56,64,65]; 3 (7%) each in the United Kingdom [27,68,69] and Korea [35,43,49]; 2 (4%) each in Italy [36,71], Turkey [41,70], Finland [44,59], Germany [54,55], and India [36,71]; and 1 (2%) each in Saudi Arabia [26], Iran [67], Serbia [66], Portugal [61], Spain [47], Singapore [38], Australia [34], and Indonesia [29]. Of the 46 studies, 32 (70%) adopted a cross-sectional study design [26,…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…Of the 46 studies, 23 (50%) focused on adults, 14 (30%) on children and adolescents, 1 (2%) on people of all ages, and the remaining 8 (17%) did not report the age range of participants. [26][27][28][29][33][34][35][36][37]39,41,[44][45][46][47][49][50][51][53][54][55][56][58][59][60][61][62][63][64][65][66][67][68]70], 8 (17%) analyzed digital image data [30,31,38,40,42,43,57,71], and 4 (9%) analyzed text data [32,48,52,69]. Obesity-related measures used across the studies included anthropometrics (eg, body weight, BMI, BFP, WC, and WHR) and biomarkers.…”
Section: Identification Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation